Endoscopic treatment of a pediatric case of choledochocele associated with choledocholithiasis - Sarac, Mehmet; Bahcecioglu, Ibrahim Halil; Tartar, Tugay; Bakal, Unal; Kazez, Ahmet (Elsevier Science Bv, 2017)
Choledochocele (type 3 choleduct cyst) is rarely seen in children. Here we report the case of a 5-year-old female who complained of abdominal pain for 2 years. A choledochocele with a diameter of 31 mm localized on the second part of the duodenum, in the periampullary region, was detected. Upper gastrointestinal endoscopy revealed a mass starting from the second part of the duodenum and constricting the duodenal lumen. A 2-cm-long incision was made at the apex of the cyst using a needle tip sphincterectome and three 5- to 6-mm stones were extracted. There were no postoperative complications. (C) 2017 The Authors. Published by Elsevier Inc. This is an open access article under the CC BY-NC-ND license.
Keywords: Choledochocele; Choledocholithiasis; Endoscopy; Choledochocelectomy